The Effectiveness of Problem-Based Learning Strategies in the Creative Thinking Skills of Grade 12 Students in Contemporary Philippine Arts from the Regions - Andal, Geraldine Q.; Hermosa, Jherwin P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This research study focused on examining the effectiveness of problem-based learning strategies in enhancing the creative thinking skills of Grade 12 students studying Contemporary Philippine Arts from the Regions. The study was conducted at the Senior High School section of Dolores Macasaet National High School, situated in Brgy. Pahinga Norte, Candelaria, Quezon Province. The participants in the study consisted of three sections from each of the three Grade 12 strands, all of whom were taught using problem-based learning methods. To facilitate the implementation of problem-based learning, the researcher created five self-made semi-detailed lesson plans covering the first five weeks of the third grading period. The research design utilized in this study was a pre-experimental one-group pre-test and post-test design. For data analysis, frequency and percentage were employed, along with mean and standard deviation calculations. Additionally, the Paired Samples T-test was utilized to compare the pre-test and post-test results. In contrast to traditional teacher-centered instruction, the problem-based learning approach adopted in this study involved presenting the problem to students first, making it a more student-centered method. This approach fostered a classroom environment that encouraged group work and collaboration, providing opportunities for students to engage in problem-based learning projects. The findings of the study revealed significant differences in the pre-test and post-test performance of the participants in terms of creative thinking skills, particularly in fluency, flexibility, originality, and elaboration, following the implementation of problem-based learning strategies.